2004
DOI: 10.1016/j.sna.2004.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Large area image sensing structures based on a-SiC:H: a dynamic characterization

Abstract: Abstract:In recent works large area hydrogenated amorphous silicon p-i-n structures with low conductivity doped layers were proposed as single element image sensors. The working principle of this type of sensor is based on the modulation, by the local illumination conditions, of the photocurrent generated by a light beam scanning the active area of the device. In order to evaluate the sensor capabilities is necessary to perform a response time characterization. This work focuses on the transient response of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Many efforts have been focused to produce light emitting devices (LEDs), PS Schottky diodes, gas sensors and solar cells using this material [6][7][8][9][10][11]. For example, Badawy [11] has reported that the solar cells based on porous silicon and covered by an oxide film, are stable against environmental attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been focused to produce light emitting devices (LEDs), PS Schottky diodes, gas sensors and solar cells using this material [6][7][8][9][10][11]. For example, Badawy [11] has reported that the solar cells based on porous silicon and covered by an oxide film, are stable against environmental attacks.…”
Section: Introductionmentioning
confidence: 99%
“…The increased responsivity of the switching diode under green bias illumination can be ascribed to a self bias process. The illuminated sensing diode, acting as a load, converts the light bias into a spatially varying electric field across the switching one [6]. This leads to a reverse self biasing of the bottom diode that switches to its OFF state becoming sensitive to the incoming scanner light.…”
Section: Discussionmentioning
confidence: 99%
“…In sensor #1 a 90 nm thermally evaporated Cr light-screening interlayer, composed of 290 · 290 lm 2 pixels with 40 lm spacing, was included. This layer prevents most (90%) of the light impinging on the switching diode from reaching the sensing one [6]. In sensor #2 the interconnection between the top and bottom junction is performed by the 50 · 50 lm 2 Cr floating contact via an a-SiN insulator layer.…”
Section: Osip Configuration and Characterizationmentioning
confidence: 99%
“…In sensor #2 a 90 nm thermally evaporated Cr light-screening inter-layer, composed by 290 · 290 lm 2 pixels with 40 lm spacing, was included. This layer prevents most (90%) of the light impinging on one diode from reaching the other one [7].…”
Section: Methodsmentioning
confidence: 99%